Potential antagonistic relationship of fgf9 and rspo1 genes in WNT4 pathway to regulate the sex differentiation in Chinese giant salamander (Andrias davidianus) - Zhang, Jiankang; Xia, Xueping; Zhu, Ying; Lian, Zitong; Tian, Haifeng; Xiao, Hanbing; Hu, Qiaomu (Frontiers in Molecular Biosciences, 2022)
Farmed chinese giant salamander (Andrias davidianus) was an important distinctive economically amphibian that exhibited male-biased sexual size dimorphism.Fgf9 and rspo1 genes antagonize each other in Wnt4 signal pathway to regulate mammal gonadal differentiation has been demonstrated. However, their expression profile and function in A. davidianus are unclear. In this study, we firstly characterized fgf9 and rspo1 genes expression in developing gonad. Results showed that fgf9 expression level was higher in testes than in ovaries and increased from 1 y to 6 y while rspo1 expression was higher in ovaries than in testes. In situ hybridization assay showed that both fgf9 and rspo1 genes expressed at 62 dpf in undifferentiated gonad, and fgf9 gene was mainly expressed in spermatogonia and sertoli cells in testis while strong positive signal of rspo1 was detected in granular cell in ovary. During sex-reversal, fgf9 expression was significantly higher in reversed testes and normal testes than in ovaries, and opposite expression pattern was detected for rspo1. When FH535 was used to inhibit Wnt/β-catenin pathway, expression of rspo1 was down-regulated. Conversely, expression of fgf9, dmrt1, ftz-f1 and cyp17 were up-regulated. Furthermore, when rspo1 and fgf9 were knocked down using RNAi technology, respectively. We observed that female biased genes were down regulated in ovary primordial cells after rspo1 was knocked down, while the opposite expression profile was observed in testis primordial cells after fgf9 was knocked down. These results suggested that fgf9 and rspo1 played an antagonistic role to regulate sex differentiation in the process of the gonadal development and provided a foundation for further functional characterizations.